2019
DOI: 10.18502/ijrm.v17i8.4820
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis B virus and hepatitis C virus infection on sperm parameters of infertile men

Abstract: Background: Viral hepatitis is one of the health problems which have the effects on the health issues. It seems that hepatitis B virus (HBV) and hepatitis C virus (HCV) infection have negative impacts on the semen quality and male infertility rate. Objective: In this study, we aimed to evaluate the effects of HBV and HCV on sperm quality among Iranian infertile men referred to Royan Institute Reproductive Biomedicine Research Center between 2003 and 2014. Materials and Methods: This retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
(18 reference statements)
2
13
0
2
Order By: Relevance
“…Among these viruses are the mumps virus (orchitis), human immunodeficiency virus-1 (orchitis and prostatitis), Coxsackie virus (epididymitis), cytomegalovirus (vesiculitis), human papillomavirus and herpes simplex virus (prostatitis) (Dejucq & Jegou, 2001). These infections lead to male infertility by increasing seminal leukocyte concentrations (Karamolahi et al, 2019;Umapathy, Simbini, Chipata, & Mbizvo, 2001;Weinberg, Sar-Shalom Nahshon, Feferkorn, & Bornstein, 2020;Wu et al, 2019). The latter virus can infect the testes and male sex accessory glands (Le Tortorec & Dejucq-Rainsford, 2010).…”
Section: Virusesmentioning
confidence: 99%
“…Among these viruses are the mumps virus (orchitis), human immunodeficiency virus-1 (orchitis and prostatitis), Coxsackie virus (epididymitis), cytomegalovirus (vesiculitis), human papillomavirus and herpes simplex virus (prostatitis) (Dejucq & Jegou, 2001). These infections lead to male infertility by increasing seminal leukocyte concentrations (Karamolahi et al, 2019;Umapathy, Simbini, Chipata, & Mbizvo, 2001;Weinberg, Sar-Shalom Nahshon, Feferkorn, & Bornstein, 2020;Wu et al, 2019). The latter virus can infect the testes and male sex accessory glands (Le Tortorec & Dejucq-Rainsford, 2010).…”
Section: Virusesmentioning
confidence: 99%
“…Several studies reported the effect of HCV on semen parameters. Lower sperm counts, abnormal morphology, reduced motility and decreased sperm lifetime were observed in HCV‐seropositive men (Hofny et al., 2011; Karamolahi et al., 2019; Lorusso et al, n.d.). Poor sperm quality and decreased sperm liquefaction time were observed in HCV‐infected men compared with non‐infected group (Karamolahi et al., 2019).…”
Section: Common Viruses Linked To Male Infertilitymentioning
confidence: 99%
“…This damage may lead to hypogonadism [42] and decrease the number of Leydig cells [43]. In similar, male infertility might initiate by several viruses such as human papillomavirus (HPV) [44], herpes simplex viruses (HSVs) [45], human immunodeficiency viruses (HIV) [46], hepatitis B virus (HBV) [47], hepatitis C virus (HCV) [48], Mumps orthorubulavirus virus (MuV) [49], and Bluetongue virus (BTV) (an arbovirus of ruminants) [50].…”
Section: Possible Mechanisms Of How the Sars-cov-2 Can Infect The Testesmentioning
confidence: 99%